Prevalência de histamina em peixes escombrídeos e intoxicação histamínica no Brasil de 2007 a 2009 - Warlley Pinheiro Evangelista (2010)
PREVALENCE OF HISTAMINE IN SCOMBROID FISH AND OF HISTAMINE POISONING IN BRAZIL FROM 2007 TO 2009. The objectives of this study were to investigate the quality of scombroid fish with respect to histamine and to investigate the occurrence of histamine poisoning. Samples of Scombroid fish were obtained during this period and analyzed for histamine by ion-pair high performance liquidchromatography with fluorimetric detection after post-column derivatization with ophthaladehyde. The samples were captured by means of long line and troll caught. The fishes mostly captured were, respectively yellowfin (Thunnus albacares) and skipjack (Katsuwonus pelamis), and swordfish (Xiphias gladius). The prevalent conditions during capture by long line were 6 to 107 days of fishing; water surfacetemperature 18.3 to 30.8 °C; depth of the bait 800 to 5500 m; number of lines - 880 to 2200; fishing area - latitude 04°47N to 22°20S and longitude 40°15W to 50°22W; and 3,320 a 195,000 kg of captured fish. The prevalent conditions during capture by troll caught were 2 to 35 days of fishing; water surface temperature 22.8 a 27.6 °C; depth of the bait - 100 to 2000 m; fishing area - latitude 22°40S to 32°44S and longitude20°11W to 48°30W; and 3,669 to 123,823 kg of fish captured. After capture, the fishes were bled, eviscerated and the flippers, head and tail were cut. Among the 864 samples analyzed, only 7.3% contained histamine at levels varying from non detected (<0.56 mg/kg) to 878.22 mg/kg (mean 5.8 mg/kg and median of 0.0 mg/kg). Only two of the 96 lots analyzed did not attend the European legislation. The levels of histamine detected were affected by the year, month of the year and region of capture. Three cases of histamine poisoning involving 25 individuals were reported in the city of Natal, RN. The symptoms included erithema, rush, vomiting, nausea and tachycardia and were observed 20-30 min after fish consumption. The samples incriminated were observed to contain 3,701.8, 750.4 and 1,565.5 mg/kg.